High Hydrostatic Pressure-Based Combination Strategies for Microbial Inactivation of Food Products: The Cases of Emerging Combination Patterns - Xia, Qiang; Liu, Qianqian; Denoya, Gabriela I.; Yang, Caijiao; Barba, Francisco J.; Yu, Huaning; Chen, Xiaojia (Frontiers in Nutrition, 2022)
The high demand for fresh-like characteristics of vegetables and fruits (V&F) boosts the industrial implementation of high hydrostatic pressure (HHP), due to its capability to simultaneously maintain original organoleptic characteristics and to achieve preservative effect of the food. However, there remains great challenges for assuring complete microbial inactivation only relying on individual HHP treatments, including pressure-resistant strains and regrowth of injured microbes during the storage process. Traditional HHP-assisted thermal processing may compromise the nutrition and functionalities due to accelerated chemical kinetics under high pressure conditions. This work summarizes the recent advances in HHP-based combination strategies for microbial safety, as exemplified by several emerging non-thermally combined patterns with high inactivation efficiencies. Considerations and requirements about future process design and development of HHP-based combination technologies are also given.